Impact of Leader-Member Exchange, Communication, Organization Commitment and Job Satisfaction on Employee Performance and Turnover Intention: A Case-Study of True Corporation Public Company Limited - Kansuwiro, Ekasit; Phinaitrup, Boon-Anan (Business Administration and Management Journal Review, 2022)
The objective of this research is to study the relationships among communication, leader-member exchanges, job satisfaction, organizational commitment, employee performance, and turnover intention. Data was collected from the sample population, who are working with True Corporation Public Company Limited, by using the paper-based questionnaires. Total of 737 questionnaires were sent out and 679 questionnaires were completed and sent back to the researcher, which equals to 95% response rate. The Structural Equation Modelling technique was used in analyzing the collected data. The result indicated that communication, leader-member exchange, job satisfaction, and organizational commitment have total effect on employee performance and turnover intention, with the statistical significance level equals to 0.01. Therefore, the organization should consider setting the communication guidelines and practices which are clear and appropriate with the communication content and objectives. In addition, supervisors and management should continuously build good relationship with employees by meeting with employees or joining activities with them. So that the organization can attract and retain high-performance employees with organization in the long run.